Molecular and enzoinformatics perspectives of targeting Polo-like kinase 1 in cancer therapy. (June 2019) - Shakil, Shazi; Baig, Mohammad H.; Tabrez, Shams; Rizvi, Syed M. Danish; Zaidi, Syed K.; Ashraf, Ghulam M.; Ansari, Shakeel A.; Khan, Aftab Aslam Parwaz; Al-Qahtani, Mohammad H.; Abuzenadah, Adel M.; Chaudhary, Adeel G.
Abstract: Cancer is a disease that has been the focus of scientific research and discovery and continues to remain so. Polo-like kinases (PLKs) are basically serine/threonine kinase enzymes that control cell cycle from yeast to humans. PLK-1 stands for 'Polo-like kinase-1'. It is the most investigated protein among PLKs. It is crucial for intracellular processes, hence a ' hot ' anticancer drug-target. Accelerating innovations in Enzoinformatics and associated molecular visualization tools have made it possible to literally perform a ' molecular level walk ' traversing through and observing the minutest contours of the active site of relevant enzymes. PLK-1 as a protein consists of a kinase domain at the protein N-terminal and a Polo Box Domain (PBD) at the C-terminal connected by a short inter-domain linking region. PBD has two Polo-Boxes. PBD of PLK-1 gives the impression of "a small clamp sandwiched between two clips", where the two Polo Boxes are the 'clips' and the 'phosphopeptide' is the small 'clamp'. Broadly, two major sites of PLK-1 can be potential targets: one is the adenosine-5′-triphosphate (ATP)–binding site in the kinase domain and the other is PBD (more preferred due to specificity). Targeting PLK-1 RNA and the interaction of PLK-1 with a key binding partner can also be approached. However, the list of potent small molecule inhibitors targeting the PBD site of PLK-1 is still not long enough and needs due input from the scientific community. Recently, eminent scientists have proposed targeting the 'Y'-shaped pocket of PLK-1-PBD and encouraged design of ligands that should be able to concurrently bind to two or more modules of the 'Y' pocket. Hence, it is suggested that during molecular interaction analyses, particular focus should be kept on the moiety in each ligand/drug candidate which directly interacts with the amino acid residue(s) that belong(s) to one of the three binding modules which together create this Y-shaped cavity. This obviously includes (but it is not limited to) the 'shallow cleft'-forming residues i.e. Trp414, H538 and K540, as significance of these binding residues has been consistently highlighted by many studies. The present article attempts to give a concise yet critically updated overview of targeting PLK-1 for cancer therapy.